Sistem Pengamanan Data Menggunakan Kriptografi AES dan Blockchain Berbasis Android - Dhiya Calista; Al Farissi; Mastura Diana Marieska (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2021)
Data or information security is a very important thing for internet users to pay attention to now, so that the data or information owned is not attacked by irresponsible parties. So, in this research, an implementation of a combination of Blockchain and AES cryptography will be carried out in order to avoid active and passive attacks by attackers. Blockchain method can detect data changes from attackers quickly and easily. However, Blockchain method can still be attacked passively, therefore AES method is combined with Blockchain as a complement that is used to encrypt data from plaintext to ciphertext so that existing data or information can be avoided from active or passive attacks. In this research, the software development method is using Rational Unified Process (RUP) method and the tests carried out are Blockchain resistance to modification attacks testing and Avalanche Effect testing on AES method. Keywords— Cryptography, Blockchain, AES, RUP, Avalanche Effect